2021
DOI: 10.3390/jcm10163506
|View full text |Cite
|
Sign up to set email alerts
|

The Reticulocyte Hemoglobin Equivalent as a Screening Marker for Iron Deficiency and Iron Deficiency Anemia in Children

Abstract: Background: Iron deficiency (ID) is one of the most common nutritional deficiencies in children worldwide and may result in iron deficiency anemia (IDA). The reticulocyte hemoglobin equivalent (Ret-He) provides information about the current availability of iron in erythropoiesis. This study aims to examine the validation of Ret-He as a screening marker for ID and IDA in children. Methods: Blood samples were retrospectively obtained from medical records. Anemia was defined according to the definition provided b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
1
11
0
1
Order By: Relevance
“…Soluble transferrin receptor (sTfR) is a fragment of TfR on the cell membrane secreted into the circulation by protease hydrolysis, which can indirectly reflect the cytosolic expression of TfR [ 85 ]. sTfR can reflect iron deficiency in anemia and inflammatory status [ 86 ]. In addition, sTfR is also a strong predictor of heart failure.…”
Section: Changes In Iron Metabolism Indicators In Iganmentioning
confidence: 99%
“…Soluble transferrin receptor (sTfR) is a fragment of TfR on the cell membrane secreted into the circulation by protease hydrolysis, which can indirectly reflect the cytosolic expression of TfR [ 85 ]. sTfR can reflect iron deficiency in anemia and inflammatory status [ 86 ]. In addition, sTfR is also a strong predictor of heart failure.…”
Section: Changes In Iron Metabolism Indicators In Iganmentioning
confidence: 99%
“…The measurement of ret-hemoglobin content is a known direct assessment of the iron incorporation into erythrocyte hemoglobin, so it is a direct estimate of the recent functional availability of such iron in the erythron [ 14 ]. A single biomarker is important to use for the diagnosis of IDA, but the use of a serum marker that can be easily identified as a screening marker is necessary [ 15 , 16 ]. Ret-He has already been suggested to be an additional marker for the screening of IDA [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A single biomarker is important to use for the diagnosis of IDA, but the use of a serum marker that can be easily identified as a screening marker is necessary [ 15 , 16 ]. Ret-He has already been suggested to be an additional marker for the screening of IDA [ 15 ]. Hence, in this study, we review the role of Ret-Hb in the diagnosis of LID and as a screening parameter for IDA.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that Ret-He can show iron deficiency without anemia. 8 , 10 , 11 Therefore, a lower value than the lower limit of the Ret-He reference range according to age indicates that an infant is iron deficient.…”
Section: Introductionmentioning
confidence: 99%